2017
DOI: 10.1002/crat.201700176
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Interface Shape in Czochralski Growth of Sapphire Crystals

Abstract: Numerical modeling is applied to investigate the factors affecting the shape of the crystal-melt interface in Czochralski growth of sapphire crystals having 10 cm in diameter. The modeling is performed for a 2D -axisymmetric furnace configuration, where all the furnace components are included. The shape of the crystal-melt interface is computed by using the deformable mesh technique. Numerical results show that the conical shape of the interface depends essentially on the internal radiative heat exchanges in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The P1 approximation model takes into account an additional heat source term in Equation that describes the radiative heat transfer for an absorbing, emitting, and scattering medium (the scattering effect is not considered in the present simulations). Numerical modeling based on this model has shown that deep convex shapes of the crystal‐melt interface are explained by the internal radiative heat exchanges . Numerical simulations in refs.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The P1 approximation model takes into account an additional heat source term in Equation that describes the radiative heat transfer for an absorbing, emitting, and scattering medium (the scattering effect is not considered in the present simulations). Numerical modeling based on this model has shown that deep convex shapes of the crystal‐melt interface are explained by the internal radiative heat exchanges . Numerical simulations in refs.…”
Section: Resultsmentioning
confidence: 98%
“…More details about the numerical and physical model used to simulate crystal growth of oxides are given in ref. []. The physical properties for sapphire and LGT are taken from refs.…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations